PERAN MOTIVASI KERJA DALAM MEMEDIASI PENGARUH GAYA KEPEMIMPINAN LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA ASN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SITUBONDO - Soeliha, Siti; Ediyanto, Ediyanto; Rifa'i, Ahmad (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The purpose of this study was to analyze the role of work motivation in mediating the influence of work environment leadership style and career development on ASN performance at the Situbondo Regency Education and Culture Office. By using the Partial Least Square (PLS) Structural equation model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that leadership style has a positive but insignificant effect on work motivation, work environment has a positive and significant effect on work motivation, career development has a positive and significant effect on work motivation, leadership style has a positive but insignificant effect on ASN performance, work environment has a negative but insignificant effect on ASN performance, career development has a positive and significant effect on ASN performance, work motivation has a positive and significant effect on ASN performance, leadership style has a positive but insignificant effect on ASN performance through work motivation, work environment has a positive but insignificant effect on ASN performance through work motivation, career development has a positive and significant effect on ASN performance through work motivation.